MALT1 Inhibition as a Therapeutic Strategy in T-Cell Acute Lymphoblastic Leukemia by Blocking Notch1-Induced NF-κB Activation - Wang, Rong; Zhang, Huihui; Xu, Jiawen; Zhang, Ninghan; Pan, Ting; Zhong, Xiaomin; Zhang, Huanxin; Yin, Lingling; Yao, Yao; Wu, Qingyun; Li, Zhenyu; Liu, Xuejiao; et al. (Frontiers in Oncology, 2020)
Current treatment of T-cell acute lymphoblastic leukemia (T-ALL) is primarily based on high-intensity combination chemotherapy which has serious side effects. Therefore, developments of novel targeted therapeutics are urgently needed for treatment of T-ALL. In this study, we found that Mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) is a novel promising therapeutic target for treatment of T-ALL. MALT1 inhibitor MI-2 significantly suppressed the cell growth, proliferation and colony formation of T-ALL cells. Furthermore, MI-2 induced cell apoptosis of T-ALL via a mitochondrial dependent pathway. In a T-ALL mouse model, MI-2 significantly reduced leukemic burden and prolonged the survival of leukemia-bearing mice. Mechanistically, MALT1 inhibition effectively blocked both baseline and Notch1-induced activation of NF-κB pathway which mediates T-ALL cell survival. In conclusion, our results highlight the potential role of MALT1 as an attractive target for treatment of T-ALL and support the potential of MI-2 or other MALT1 inhibitors to clinical trials in T-ALL.